An evaluation of the effectiveness of sumac and molasses as additives for alfalfa silage: Influence on nutrient composition, in vitro degradability and fermentation quality - Tatli Seven, Pinar; Yildirim, Esra Nur; Seven, Ismail; Kaya, Can Ayhan; Iflazoglu Mutlu, Seda (Wiley, 2024)
This study investigated the effects of sumac and molasses on nutrient composition, in vitro degradability and fermentation quality of alfalfa silage. Alfalfa was ensiled in quadruplicate in vacuum jars untreated group (A) or after the following treatments: sumac group at 10% (AS), molasses group at 5% (AM), and sumac (10%) and molasses (5%) group (ASM). Silos (n = 64) were stored for 0, 21, 45 or 60 days. The results showed that dry matter (DM) contents of the AS, AM and ASM groups were statistically higher than the control group (p < 0.001). Only on the 21st day of fermentation the crude ash content of the AS group was found to be significantly higher than the other groups (p < 0.05). In vitro, DM and organic matter degradation values of the AMS group increased significantly (p < 0.001). A significant decrease in alfalfa silage's pH values was determined with sumac and molasses additives (p < 0.001). The ammonia nitrogen (NH3-N) values of the control, AS, AM and ASM groups at Day 60 were determined as 9.08%, 7.22%, 7.00% and 6.81% respectively (p < 0.05). The water-soluble carbohydrate (WSC) values of all groups on the 60th day were significantly decreased compared to the 0th day (p < 0.001). When the groups were evaluated within themselves, there was a statistically significant difference between the 0th and 60th day lactic acid values. The acetic acid content of the A group on the 60th day was found to be significantly higher than the other groups (p < 0.01). There was a significant decrease in propionic acid levels on Days 21, 45 and 60 compared to Day 0 of fermentation (p < 0.001). The highest butyric acid (BA) level was determined in the A group on the 21st, 45th and 60th days of fermentation (p < 0.05). In conclusion, sumac prevents proteolysis depending on its tannin content. It improves silage fermentation positively thanks to its organic acid content, while the molasses additive is effective in silage fermentation, mainly depending on the WSC level. However, it was determined that neither additive could reduce the silage pH to the appropriate value ranges due to the low doses, and they could not mainly prevent the formation of BA.
Keywords: alfalfa silage; fermentation quality in vitro degradability; molasses; proteolysis; sumac